Hope and challenge: Precision medicine in bladder cancer - Hongwei Su; Haitao Jiang; Tao Tao; Xing Kang; Xu Zhang; Danyue Kang; Shucheng Li; Chengxi Li; Haifeng Wang; Zhao Yang; Jinku Zhang; Chong Li (Cancer Medicine, 2019)
Abstract Bladder cancer (BC) is a complex disease and could be classified into nonmuscle‐invasive BC (NMIBC) or muscle‐invasive BC (MIBC) subtypes according to the distinct genetic background and clinical prognosis. Until now, the golden standard and confirmed diagnosis of BC is cystoscopy and the major problems of BC are the high rate of recurrence and high costs in the clinic. Recent molecular and genetic studies have provided perspectives on the novel biomarkers and potential therapeutic targets of BC. In this article, we provided an overview of the traditional diagnostic approaches of BC, and introduced some new imaging, endoscopic, and immunological diagnostic technology in the accurate diagnosis of BC. Meanwhile, the minimally invasive precision treatment technique, immunotherapy, chemotherapy, gene therapy, and targeted therapy of BC were also included. Here, we will overview the diagnosis and therapy methods of BC used in clinical practice, focusing on their specificity, efficiency, and safety. On the basis of the discussion of the benefits of precision medicine in BC, we will also discuss the challenges and limitations facing the non‐invasive methods of diagnosis and precision therapy of BC. The molecularly targeted and immunotherapeutic approaches, and gene therapy methods to BC treatment improved the prognosis and overall survival of BC patients.